Excision of a giant lipoma in the neck region under ultrasound-guided cervical plexus block: a case report - Torun, Mümtaz Taner; Akyol, Fethi; Seçkin, Ender (International Journal of Research in Medical Sciences, 2017)
Lipomas are slow-growing benign soft-tissue tumors which are typically asymptomatic. The ultrasound-guided cervical plexus block (UGCPB) is a feasible, effective and safe method for ear, neck (especially thyroid operations and carotid endarterectomy) and clavicular region surgery. It can be used in cases with a high risk for general anesthesia. A case of a giant neck lipoma excised using UGCPB is reviewed in this paper. A 56-year-old male patient presented to our clinic with a giant mass 11x10 cm in size in the right neck region. A mobile, smooth surfaced and painless lump was detected. The mass was preoperatively reported as a lipoma. The patient had a high cardiovascular risk for general anesthesia. The mass was too large for excision with infiltration anesthesia, so we decided to perform UGCPB. UGCPB can be used with patients with a high general anesthesia risk. The type of CPB can be selected depending on the region to be operated in order to avoid complications. We operated using intermediate UGCPB. This technique is feasible, effective and comfortable. It is also more reliable than general anesthesia.